Microsatellite Characterization of Malaysian Mahseer (Tor spp.) for Improvement of Broodstock Management and Utilization - Poh Chiang Chew; Annie Christianus; Jaapar M. Zudaidy; Md Yasin Ina-Salwany; Chou Min Chong; Soon Guan Tan (Animals, 2021)
In this study, a mixture of Tor tambra and T. tambroides with unknown genetic background were collected from 11 localities in Malaysia for broodstock development and sperm cryo-banking. This study aims to assess the microsatellite (simple sequence repeat, SSR) variation, genetic diversity, genetic differentiation, level of gene flow, population structure, genetic relatedness and their demographic aspects among these Tor populations, in addition to establishing their SSR profile by employing 22 SSR markers via fragment analysis. Total genomic DNA was extracted from 181 samples (91 cryopreserved milt samples and 90 scale samples of live broodfish). Results showed the Tor spp. collection retained their genetic variation but exhibited excessive homozygosity among individuals within population. Moderate genetic differentiation was shown among the populations, with highly significant (p < 0.001) fixation indices (FST, FIS and FIT). A low gene flow over all loci (Nm 1.548) indicates little genetic variation transfer between populations. The genetic structures of all the populations were successfully resolved into four main clusters by an unweighted pair group method with arithmetic mean (UPGMA) dendrogram generated based on Nei’s genetic distances. The population structures based on principal coordinates analysis (PCoA) and the Bayesian model also suggested four distinct clusters following geographical regions and eight closely related populations. This study provided a useful baseline reference for better genetic management and utilization of the Tor spp. stocks in their breeding and conservation programmes.